Pengaruh Kompetensi dan Budaya Kerja terhadap Kinerja di Perusahaan Umum Daerah Pasar Jaya - Rachim, Imaduddin Abdul; Ruhana, Faria; Meltarini, Meltarini (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The purpose of this study was to examine the influence of organizational culture, competence, and performance both partially and simultaneously.The method used in this research is path analysis method. The object population of the study was 94 employees, sampling using slovin methods. The research results show that there is an influence of competence on the performance of Perumda Pasar Jaya employees. This influence is quite significant and indicates that there is a causal relationship between competence and the performance of Perumda Pasar Jaya employees. There is an influence of work culture on the performance of Perumda Pasar Jaya employees. This influence is quite significant and indicates that there is a causal relationship between work culture and the performance of Perumda Pasar Jaya employees. There is a simultaneous influence of competence and work culture on the performance of Perumda Pasar Jaya employees.